Rapid synchronous synthesis of Ag nanoparticles and Ag nanoparticles/holocellulose nanofibrils: Hg(II) detection and dye discoloration. (15th July 2020) - Bandi, Rajkumar; Alle, Madhusudhan; Park, Chan-Woo; Han, Song-Yi; Kwon, Gu-Joong; Kim, Jin-Chul; Lee, Seung-Hwan
Graphical abstract: Highlights: Ag nanoparticles (AgNPs) and AgNPs/holocellulose nanofibrils produced synchronously. Rapid microwave assisted synthesis (60 s) without using a reducing agent. Colloidal AgNPs used for the colorimetric detection of Hg(II) in real water samples. Catalytic discoloration of organic dyes over AgNPs/holocellulose nanofibrils aerogel. Easy recovery and high efficiency over multiple discoloration cycles. Abstract: A novel microwave-assisted green method that synchronously synthesizes silver nanoparticles (AgNPs) and AgNPs decorated holocellulose nanofibrils (AgNPs/HCNF) within a minute and without using a reducing agent is reported. As obtained nanomaterials were well characterized using various analytical techniques. AgNPs applied as a colorimetric probe for the selective recognition of Hg(II) (linear range 10–200 μg L −1, detection limit 1.16 μg L −1 ). The probe was able to quantify Hg(II) in spiked tap, bore, and lake water samples and paper strips were developed to facilitate the onsite detection. Furthermore, freeze-drying of the AgNPs/HCNF nanocomposite produced aerogel that served as an excellent catalyst for the reduction of Congo red and methylene blue. The aerogel was easily recovered and reused without a decrease in activity or deterioration of its structure for five cycles. These results indicate the great potential of the AgNPs/HCNF aerogel for waste water treatment and catalytic applications.